2016
DOI: 10.1016/j.ophtha.2015.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Spectralis and Cirrus Reference Databases in Differentiating between Healthy and Early Glaucoma Eyes

Abstract: Purpose To evaluate and compare the diagnostic accuracy of the global and sector analyses for detection of early visual field damage using the retinal nerve fiber layer (RNFL) reference databases of the Spectralis and Cirrus spectral-domain optical coherence tomography (SD-OCT) devices. Methods Healthy subjects and glaucoma suspects from the Diagnostic Innovations in Glaucoma Study (DIGS) and African Descent and Glaucoma Evaluation Study (ADAGES) with at least 2 years of follow-up were included. Global and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
0
23
0
3
Order By: Relevance
“…Automated or manual multilayer segmentation of the retina [1619] in clinical practice is constantly increasing, and topographic thickness map measurements provide valuable information about retinal cell layers [20,21]. For example, certain studies have shown that ganglion cell layer (GCL) thickness reduction is associated with visual function and can predict disease severity in multiple sclerosis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Automated or manual multilayer segmentation of the retina [1619] in clinical practice is constantly increasing, and topographic thickness map measurements provide valuable information about retinal cell layers [20,21]. For example, certain studies have shown that ganglion cell layer (GCL) thickness reduction is associated with visual function and can predict disease severity in multiple sclerosis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The RNFL thickness values for a scan are classified using a 6-sector analysis, and sectors can be flagged green ("Within Normal Limits"), yellow ("Borderline"), and red ("Outside Normal Limits"). RNFL parameters of the SPECTRALIS have been evaluated relative to other commercially available SD-OCT devices and shown to be as specific, sensitive, and repeatable [51,52].…”
Section: Spectralis Sd-octmentioning
confidence: 99%
“…Da die normale Papillengröße, RNF-Dicke und Ganglienzellschichtdicke zwischen Kaukasiern, Afrikanern, Asiaten und Indern unterschiedlich sein können, berücksichtigen einige Datenbanken verschiedene Ethnien, sodass vor der Bildaufnahme die Ethnie des Patienten mit angegeben werden muss. Silverman et al [4]…”
Section: Normwerte Der Rnf Mit Dem Octunclassified